2016
DOI: 10.1037/rel0000025
|View full text |Cite
|
Sign up to set email alerts
|

Examining whether spirituality predicts subjective well-being: How to avoid tautology.

Abstract: Spirituality may help people to maintain a high level of well-being despite adversity, but several studies that claim to support this statement have used spirituality scales and outcome measures that have overlapping content. This practice seems to be widespread: In an exploratory survey of eight well-cited journals we found that 26 of 58 studies used a spirituality scale that contains 25% or more of well-being items to examine whether spirituality predicts well-being or distress. These spirituality questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 71 publications
4
26
0
3
Order By: Relevance
“…The overlap between these measures will artificially increase the strength of their association [31], so one may wrongly conclude that personal meaning leads to psychological well-being or vice versa. Furthermore, measuring both constructs increases the problem of multiple testing, because the same phenomena are measured more often.…”
Section: Discussionmentioning
confidence: 99%
“…The overlap between these measures will artificially increase the strength of their association [31], so one may wrongly conclude that personal meaning leads to psychological well-being or vice versa. Furthermore, measuring both constructs increases the problem of multiple testing, because the same phenomena are measured more often.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, spiritual well-being is a complex construct, often perceived as comprising of four domains, e.g., by National Interfaith Coalition on Aging (NICA), Fisher (1998), Waaijman (2006, and Garssen et al (2016). Each of the items in the 4-ISWB Index provides a summary view of respondents' perceptions of the quality of relationships in each of the four specified areas, which constitute SWB, and not just a title.…”
Section: Discussionmentioning
confidence: 99%
“…Moberg (2011) lists eighteen different types of spirituality, and Koenig et al (2001Koenig et al ( , 2012 add even more. On top of this uncertainty, controversy also surrounds the relationship between spirituality and well-being, with some authors claiming that spirituality is usurping or duplicating areas more appropriately related to psychology or sociology (Garssen et al 2016;Koenig 2008;MacDonald et al 2015). The influence of spirit on health has been a point of discussion from around 400BC, in Hippocrates' time (Adams 1939), as well as in Chinese medicine.…”
Section: Holistic/spiritual Well-being and Educationmentioning
confidence: 99%
“…Increased secularism in Western culture has seen a decrease in the overtly religious connotations of the term spiritualty (Chochinov & Cann, 2005), and empirical studies have demonstrated that religiousness and spiritualty are independent dimensions (Saucier & Skrzypińska, 2006). Indeed, spirituality is increasingly being recognized as an important facet of many people's lives, including those who do not adhere to a particular set of religious beliefs (Garssen, Visser, & de Jager Meezenbroek, 2016). Thus, it has been argued that spirituality is a broader concept than religion, which may be seen as institutionalized codifications through which one's spirituality may be articulated (Brady, Peterman, Fitchett, Mo, & Cella, 1999).…”
Section: Spiritualitymentioning
confidence: 99%